2019
DOI: 10.1029/2019jd030631
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Role of Midtropospheric Cyclonic Vortex in the Formation of Super Typhoon Nepartak (2016)

Abstract: Based on a successful cloud‐resolving simulation with the Weather Research and Forecasting Model, this study examines the evolution and the role of midtropospheric mesoscale cyclonic vortex in the formation of Super Typhoon Nepartak (2016). The midtropospheric vortex is correlated with the convective activity in pre‐Nepartak. Once the deep convection outbreaks, the midtropospheric vortex intensifies first via the vertical advection associated with the severe updrafts and then through the midlevel convergence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Although tropical cyclogenesis is usually marked as the formation of a well‐defined surface vortex center, lots of observational and numerical studies have shown that a coherent mid‐level vortex often precedes the TC genesis (e.g., Bister & Emanuel, 1997; McBride & Zehr, 1981; Nolan, 2007; Simpson et al., 1997; Tang et al., 2020; Wu & Fang 2019). For example, from 1998 to 2001 88% of TCs developing in the Atlantics and the Northeastern Pacific show intensification of the mid‐level circulation before genesis (Dunkerton et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although tropical cyclogenesis is usually marked as the formation of a well‐defined surface vortex center, lots of observational and numerical studies have shown that a coherent mid‐level vortex often precedes the TC genesis (e.g., Bister & Emanuel, 1997; McBride & Zehr, 1981; Nolan, 2007; Simpson et al., 1997; Tang et al., 2020; Wu & Fang 2019). For example, from 1998 to 2001 88% of TCs developing in the Atlantics and the Northeastern Pacific show intensification of the mid‐level circulation before genesis (Dunkerton et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zehr (1992) proposed a two-stage formation process, during which a deep convection cycle was followed by another until genesis occurs. Such multiple convective burst events leading up to TC genesis were confirmed in the satellite observations (e.g., Chang et al, 2017;Davis & Ahijevych, 2012) and numerical simulations (e.g., Fang & Zhang, 2010;Wang, 2014a;Wu & Fang, 2019). They are also referred to as quasi-periodic features.…”
mentioning
confidence: 63%
“…The prefix “quasi‐” indicates that the intervals between burst events are not strictly fixed like sine and cosine waves. These quasi‐periodic features were often treated as diurnal variations modulated by the solar radiation (Chang et al., 2017; Nam & Bell, 2021; Wang, 2018; Wu & Fang, 2019; Zawislak & Zipser, 2014). Diurnal cycle in radiative forcing affects convection in many ways.…”
Section: Introductionmentioning
confidence: 99%